Experimental Research of the Mechanical Properties of the Injection Molded Parts in Molds Produced By Additive Manufacturing - Tuteski, Ognen; Kochov, Atanas (University Ss. Cyril and Methodius in Skopje, 2023)
In this study, additive manufacturing emerges as an innovative technology for concurrent engineering in the design and production of molds for injection molding processes. The primary objective is to conduct experimental research on the mechanical properties of injection-molded parts using a non-conventional mold produced through additive manufacturing technologies. The state-of-the-art additive manufacturing technologies provide various methodologies and techniques for designing and printing parts. Utilizing these diverse technologies significantly expands the possibilities for rapidly creating molds, thereby enhancing the scope of rapid tooling in the molding process. The study begins by designing and fabricating SLA mold inserts according to the relevant tensile testing standards. To evaluate the mechanical properties, a series of tensile tests are conducted and a comparison is made between the properties of the molded parts produced with SLA mold inserts. The results demonstrate that SLA mold inserts made with additive manufacturing can effectively produce injection molded parts with comparable tensile strength to those manufactured using traditional steel molds.
Keywords: additive manufacturing, injection molding, rapid tooling, stereolithography, tensile testing